2023
DOI: 10.1021/acsomega.3c06239
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Proteins as Delivery Vehicles for PFAS Contaminants into Respiratory Membranes

Evan S. Pye,
Shannon E. Wallace,
D. Gerrard Marangoni
et al.

Abstract: Poly- and perfluoroalkyl substances (PFAS) are a family of chemicals that have been used in a wide range of commercial products. While their use is declining, the prevalence of PFAS, combined with their chemical longevity, ensures that detectable levels will remain in the environment for years to come. As such, there is a pressing need to understand how PFAS contaminants interact with other elements of the human exposome and the consequences of these interactions for human health. Using serum albumin as a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(75 reference statements)
0
0
0
Order By: Relevance
“…The pulmonary epithelium and the layer of lung surfactants (LS) covering the cells are the primary portal of inhaled pollutants, creating a physical barrier of entry between the outside environment and blood circulation [23]. In the study of Pye et al [24], it was shown that environmental protein contained in dust particles inhaled can act as a transport carrier of PFASs into the respiratory system, modifying the lung surfactant function and inducing pro-inflammatory and allergic responses [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The pulmonary epithelium and the layer of lung surfactants (LS) covering the cells are the primary portal of inhaled pollutants, creating a physical barrier of entry between the outside environment and blood circulation [23]. In the study of Pye et al [24], it was shown that environmental protein contained in dust particles inhaled can act as a transport carrier of PFASs into the respiratory system, modifying the lung surfactant function and inducing pro-inflammatory and allergic responses [25][26][27].…”
Section: Introductionmentioning
confidence: 99%